2010
DOI: 10.1136/ard.2009.117309
|View full text |Cite
|
Sign up to set email alerts
|

Association between anti-tumour necrosis factor treatment response and genetic variants within the TLR and NFκB signalling pathways

Abstract: Several SNPs mapping to the TLR and NFkappaB signalling systems demonstrated association with anti-TNF response as a whole and, in particular, with response to etanercept. Validation of these findings in an independent cohort is now warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 25 publications
5
43
0
Order By: Relevance
“…There are only a few studies of the presence or functional role of this polymorphism in human disorders. MyD88 rs7744 has been associated with autoimmune or inflammatory processes, [52][53][54] but its biological function has not yet been identified. As it is located in the 3' untranslated region (UTR) region, MyD88 rs7744 could influence the stability of mRNA, thereby compromising normal protein levels.…”
Section: E53mentioning
confidence: 99%
“…There are only a few studies of the presence or functional role of this polymorphism in human disorders. MyD88 rs7744 has been associated with autoimmune or inflammatory processes, [52][53][54] but its biological function has not yet been identified. As it is located in the 3' untranslated region (UTR) region, MyD88 rs7744 could influence the stability of mRNA, thereby compromising normal protein levels.…”
Section: E53mentioning
confidence: 99%
“…In addition, this minor allele homozygote was associated with the disease severity of UC, hospitalization and response to steroid treatment. Potter et al have reported that rs7744 is nominally associated with a response to anti-TNF therapy for rheumatoid arthritis (29). This evidence indicates that rs7744 may be associated with a response to treatment for UC.…”
Section: ------------------------------------------------------------mentioning
confidence: 84%
“…SNPs located within the TLR and NF-ĸB pathways such as rTLR signalling protein MyD88 (rs7744) and kinase CHUK (rs11591741) have been demonstrated to be associated with good response to anti-TNF therapy [36]. MyD88 and CHUK play integral roles in the NFĸB signalling system, effecting TNF production and chronic inflammatory processes [37,38].…”
Section: Theranostic Biomarkers and Response To Anti-tnf Therapymentioning
confidence: 99%